Pengelolaan Sampah Melalui Bank Sampah Untuk Meningkatkan Taraf Perekonomian Masyarakat - Muhammad Imaaduddin; Masjunaidi Masjunaidi; Amir Husin; Mardhiah Mardhiah (LPPM Universitas Internasional Batam, 2023)
Along with the increase in population in Tanjungpinang City, it also has an impact on the environment that is polluted by household waste that is left to accumulate in landfills and is not properly processed. Even though the waste can be processed or resold and can generate an economy that will help improve the standard of living of the community. Community service activities carried out in the form of helping to provide socialization and training on how to manage household waste into materials of economic value and practice how to form a Waste Bank unit so that the community can be independent in processing waste and become a means of saving by using waste so that people are more motivated to maintain cleanliness. The method used in this service is the PAR method where we help invite the community to actively participate in solving the problems faced, namely waste, and the results of this study are that the community in rt.3 rw.3 kelurahan tanjung ayun sakti, tanjungpinang managed to create a waste bank unit and can maximize household waste into rupiah coffers, and it is hoped that the role of the government will also help support the development of this Waste Bank.